Conduction content-analysis based literature review in operations and supply chain management - Seuring, Stefan; Gold, Stefan; Beske, Philip; Liu, Y; Morana, Romy; Li, W (My University, 2009)
Seuring S, Gold S, Beske P, Liu Y, Morana R, Li W..
, 2009